Comparative Study of Biofilm and Non-Biofilm Producing Klebsiella pneumoniae with Special Reference to Metallo-Beta-Lactamase Production - Prajakta S. Pawar; Satyajeet K. Pawar; Satish R. Patil; Harsha V. Patil; Priyanka M. Mane (Journal of Pure and Applied Microbiology, 2024)
Klebsiella pneumoniae is one of the most common bacteria among all biofilm-producing as well as the beta-lactamase producing strains, which is responsible for multi-drug resistance. For better therapeutic applications, it is important to detect the biofilm production by Klebsiella pneumoniae and their antibiogram along with the ability to produce ESBL, MBL, and AmpC β-lactamases. The aim of the study was to determine the prevalence of biofilm formation and ESBL, MBL, AmpC β-lactamase phenotypes in K. pneumoniae as well as the antibiogram of all (biofilm and MBL-producing and non-producing) isolates of K. pneumoniae. Isolates of K. pneumoniae were tested for biofilm formation by the Congo-red agar method. ESBL, MBL, and AmpC β-lactamase detection were done by both screening and confirmatory tests as per CLSI guidelines. The antibiogram was obtained by the Kirby-Bauer disc diffusion method. Among the total 100 isolates of K. pneumoniae, 40% were biofilm-producing. Most of them were from urine specimens. Out of biofilm-producing isolates, ESBL – 28%, MBL- 47% and AmpC β-lactamase- 25.8% producers were observed. K. pneumoniae isolates were seen to have maximum resistance to ceftazidime and maximum sensitivity to nitrofurantoin. Study findings suggest the importance of assessment of biofilm formation for better treatment. The scenario further worsens if such biofilm-producing isolates are also MBL-positive leading to limited therapeutic options.